2012
DOI: 10.1007/s00114-012-0915-3
|View full text |Cite
|
Sign up to set email alerts
|

First ceratosaurian dinosaur from Australia

Abstract: The basal theropod dinosaur clade Ceratosauria, and its subclade Abelisauroidea, is characteristic of late Mesozoic terrestrial vertebrate faunas in western Gondwana (South America, Africa, Madagascar, and India) and Europe. Yet unambiguous records of ceratosaurs have hitherto been absent from Australia, where the theropod assemblage appears to include several typically Laurasian clades. Here, we report the first evidence of ceratosaurs (and potentially abelisauroids) from eastern Gondwana--a diagnostic astrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
1
19
1
Order By: Relevance
“…After a comprehensive phylogenetic analysis, these authors considered megaraptorans as allosauroids closely related with carcharodontosaurid theropods, an interpretation subsequently followed by later authors (Carrano et al, 2012;Zanno and Makovicky, 2013). However, recent studies conducted by some of us (e.g., Novas et al, 2013;Porfiri et al, 2014) have suggested that megaraptorans are not representative of archaic allosauroid tetanurans, but instead argued that megaraptorans are coelurosaurs, and representatives of a basal tyrannosauroid radiation in particular (Novas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a comprehensive phylogenetic analysis, these authors considered megaraptorans as allosauroids closely related with carcharodontosaurid theropods, an interpretation subsequently followed by later authors (Carrano et al, 2012;Zanno and Makovicky, 2013). However, recent studies conducted by some of us (e.g., Novas et al, 2013;Porfiri et al, 2014) have suggested that megaraptorans are not representative of archaic allosauroid tetanurans, but instead argued that megaraptorans are coelurosaurs, and representatives of a basal tyrannosauroid radiation in particular (Novas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additional evidence of the presence of megaraptorids in regions of South America other than Argentina comes from Brazil, from which isolated caudal vertebrae have been described (Mendez et al, 2013). Cretaceous formations of Australia have yielded several isolated elements referred to Megaraptoridae, including Rapator ornitholestoides (Huene, 1932;Agnolín et al, 2010;White et al, 2012), an isolated ulna closely similar to that of Megaraptor and Australovenator (Smith et al, 2008), more than one hundred isolated teeth (Benson et al, 2012), and probably an isolated astragalus (Molnar et al, 1981;Fitzgerald et al, 2012), and paired pubes originally described as tyrannosauroid (Benson et al, 2010b;Novas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…. There are also various disputed Early Cretaceous (Aptian-Albian) possible ceratosaur remains from Australia (reviewed by , and a definite ceratosaur astragalus (Fitzgerald et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Dietrich et al (2014) dated the split of I. uriae and I. holocyclus when Australia and Antarctic was still connected and available mammal hosts there were monotremes (Archer et al, 1985;Musser, 2003). Avialae was established by early Cretaceous in Australasia (Chiappe, 1996;Close et al, 2009;Fitzgerald et al, 2012;Martin et al, 2014) and by late Cretaceous in Antarctica (Chiappe, 1996;Clarke et al, 2005) therefore this split event should have occurred in Australasia coinciding with the origin of I. uriae proposed by Dietrich et al (2014). Probably Australasian Ixodes uriae passed the K-Pg boundary feeding on MB and Ixodes holocyclus or their ancestors, surpassed it as a parasite of Monotremata (eventually on early Australian marsupials or both).…”
Section: Hypothesis About Evolution Of the Australasian Ixodes + Uriamentioning
confidence: 99%